Learning management and formative practice of Ecuadorian teachers (Revista Innova Educación, 2021)
The purpose of this study was to determine the level of relationship that exists between learning management and the formative practice of teachers. The design was of cross-correlation with a descriptive approach, where 66 students from the Dolores Cacuango Educational Unit, Cantón Guayaquil, Parroquia Tarqui participated in the period 2017, being the instrument used the survey, this was aimed at teachers and students of the educational institution. The results obtained in this research agree that the training practice is directly linked to management, this being the backbone of the Institution's success, for this the leadership of the director and the support of the entire community were taken into account educational, to parents, students and / or students and community. It is concluded that there is a high level of relationship between learning management and training practice.
Keywords: Education; teaching; practice; training; dimensions